An enantioselective synthesis of α-alkylated pyrroles via cooperative isothiourea/palladium catalysis. Issue 7 (28th November 2018) - Rush Scaggs, W.; Scaggs, Toya D.; Snaddon, Thomas N.
Abstract : Herein we describe the direct enantioselective Lewis base/Pd catalysed α-allylation of pyrrole acetic acid esters. Abstract : Herein we describe the direct enantioselective Lewis base/Pd catalysed α-allylation of pyrrole acetic acid esters. This provides high isolated yields of highly enantioenriched products and exhibits broad reaction scope with respect to both reaction partners. The products can be readily elaborated in a manner which points towards potential applications in target directed synthesis.